Updating reviews: We discussed best practice at the EAHIL 2022 Conference (Journal of EAHIL, 2022)
We conducted a workshop at the EAHIL 2022 Conference which aimed to identify best practice when updating literature searches for systematic reviews. We prepared a presentation and questions which were discussed in small groups. The potential solutions were evaluated using the “rose, thorn, bud” method, and the results of the workshop are summarised here. The importance of transparently reporting the search strategies, platforms, and changes compared to previous searches were emphasised. Workshop participants preferred to change (and improve) previous strategies rather than repeating faulty searches. They also preferred to re-run searches over the whole time period instead of searching from a time point on, suggesting deduplication methods to manage the records. We hope this discussion will continue at future conferences.